Serviceundersökningen: Äldreomsorg i fem typkommuner 1993 - Lennart Nilsson; Vicki Johansson; Lars Strömberg (Swedish National Data Service, 1995)
This survey was carried out within the framework of the research programme ´Demokrati i förändring´. The survey was carried out in four municipalities; Grästorp, Kävlinge, Lidköping and Luleå, and in one district of Göteborg, Centrum. The choice of municipalities was made with regard to the classification of municipalities done in the citizen survey of the research programme, Local citizen survey 1991 (SSD 0306). The survey was directed towards persons aged 65-85. The questionnaire contained questions about marital status; size of household; number of sons and daughters; distance to children´s home; how often one sees the children or speaks with them on the telephone; opinion on how public old-age care ought to be worked out; economic aid to alternative old-age care; economic aid to elderly. For some twenty areas the respondents had to state if they took care of them themselves or if they were assisted by someone; if they were assisted by home-help; at what time they were assisted by someone else; opinion on the public old-age care; and monthly cost for old-age care. A number of questions dealt with attitude towards the public old-age care and its personnel; opinion of the assistance in general, if one needs more assistance and from whom one would like assistance; distribution of old-age care between various groups of elderly, and under what circumstances one is prepared to pay for old-age care. The questionnaire also included questions on how often the respondent, and spouse if any, used medical care and transportation service during the last six months; opinion of the distribution of medical care between various groups; and under what circumstances one is prepared to pay for medical care. The respondents also had to state their opinion on local authority services in various areas; service areas most important to focus on and service areas possible to cut down; opinion on local authority service in general; and experience of their own contacts with local government officers within the old-age care department. ...